A study of prevalence of Anopheline mosquitoes from a periurban locality of Bareilly District, India - Atul Kumar3, Shatrughan Singh1, Ramesh Chandra2 and (Journal of Experimental Sciences, 2010)
<div style="border-right: medium none; padding-right: 0in; border-top: windowtext 1pt solid; padding-left: 0in; background: white; padding-bottom: 0in; border-left: medium none; padding-top: 1pt; border-bottom: medium none; mso-element: para-border-div; mso-border-top-alt: solid windowtext .5pt;"> Abstract Mosquitoes are dipterans causing transmission of harmful diseases viz. Malaria, Filaria, Encephalitis, Dengue etc. These are hematophagous insects. These are attracted towards hosts mainly in night but attack in day time also, thus the feeding behaviour is studied in night easily. Anopheline species from human and cattle dwellings were studied during Nov. 2006 to Feb. 2006. Out of 1210 specimens, a total number of 819 Anopheline mosquitoes representing 9 species were identified. These were identified on the basis of ornamentation of wings and palpi. Observed species An. culicifacies (13%) and An. splendidus (16%) were found abundant in cattle shades while An. stephensi (11%) An. vagus (5%) and An. subpictus (8%) were abundant in human dwellings and the maximum frequency of An. maculatus (19%), An. annularis (12%), An. fluviatilis (8%), and An. pulcherrimus (7%) was seen in mixed dwellings. Key words: Physico-chemical parameters, Water quality, Phytoplanktons, Kohargaddi dam 1Department of Zoology, J. P. M. College, Bareilly (U.P.), India; 2S. S. (P.G.) College, Shahjahanpur (U.P.), India; 3Bareilly College, Bareilly (U.P.), India Please Cite This Article As: Shatrughan Singh, Ramesh Chandra and Atul Kumar. 2010. A study of prevalence of Anopheline mosquitoes from a periurban locality of Bareilly District. J. Exp. Sci. 1(5):17.